(untitled) (Práxis Educativa, 2019)
This paper reflects upon today’s context of Physical Education in Brazil. Based on an essay written by Bernard Charlot in the field of Pedagogy, we conducted analogies with the area in order to present how we see it in the form of three great thoughts. In a second moment, we present a current epistemological mapping of the field, in order to show the diversity of its knowledge from a post-critical referential. We decentralize the role of the academic knowledge, enhancing that belonging to common sense and popular culture, a fact that transforms body culture, object of the field. This argument leads us, finally, to extol the importance of post-critical thinking in Physical Education, to question the institutional insistence of its maintenance exclusively in the Coordination for the Improvement of Higher Education Personnel (CAPES) Evaluation Area 21 and to present the negative consequences of this process for students, teachers and researchers. Keywords: Epistemology. Post-critical theory. CAPES.